The Effects of Out‐of‐Regime Guidance on Auditor Judgments About Appropriate Application of Accounting Standards1. (30th December 2016) - Scott Asay, H.; Brown, Tim; Nelson, Mark W.; Jeffrey Wilks, T.
Abstract: Accountants making judgments with respect to a particular set of standards are increasingly aware of standards from other reporting regimes that offer additional or conflicting guidance. In fact, IFRS encourages reliance on out‐of‐regime standards when IFRS lacks guidance. This paper reports the results of two experiments which provide evidence that auditors in such circumstances are vulnerable to contrast effects, whereby reporting judgments under IFRS are systematically influenced away from the accounting treatment supported by standards from another regime (U.S. GAAP). Contrast effects are observed (i) when out‐of‐regime standards are considered before making a reporting judgment under IFRS, and (ii) when out‐of‐regime standards are applied as local GAAP for a subsidiary of a foreign parent that reports under IFRS. We also find that contrast effects are reduced when auditors believe IFRS lacks guidance. These results have implications for financial statement preparers and auditors in the current incomplete‐convergence environment.